THE COLONIALITY OF GENDER IN SPORTS AND EDUCATION: COLONIAL LEGACIES OF THE PHILIPPINES’ MODERN GENDER SYSTEM IN ROOKIE (2023) - Pratiwi, Hestia Dwi; Darmoko, Darmoko (International Review of Humanities Studies, 2025)
This article discusses the lasting impact of colonial-era policies on the gender system portrayed in the Filipino LGBT coming-of-age movie "Rookie" (2023) by analyzing the gendered notions in sports and education. Rookie, directed by Samantha Lee, tells the story of Maria "Ace" Asuncion who is navigating and exploring life as a transfer student learning to master volleyball. As a rookie or newbie at school and in the sport, Ace comes across gendered notions in sports and education that reveal the state of the gender system. Using the concept of 'Coloniality of Gender' by Maria Lugones, this paper argues how colonial policies impact the gender system by examining gendered notions whose origin can be traced to the history of colonialization in the Philippines by Spain and the United States. Rookie shows the current picture of the enduring influence of colonial-era policies on the gender system through its portrayal of sports and education. However, the movie also portrays how the main characters defy from heterosexualist gendered notions through an exploration of their sexuality.